Kepimpinan dan pengurusan strategik di institusi pendidikan MARA - Mariam Md. Salleh,; Mohammed Sani Ibrahim,; Siti Rahayah Ariffin, (penerbit ukm, 2009)
The purpose of this study is to examine the leadership and strategic management at various MARA educational institutions, namely MARA Professional Colleges (KPM)/MARA Colleges (KM), MARA Vocational Institution (IKM) and MARA Junior Science Colleges (MRSM). Data was obtained through a survey questionnaire on 425 management personnels and interviews on 15 respondents. Generally the leadership and strategic management level are high. MANOVA analysis shows significant differences in leadership between IKM and MRSM. There has been an interactive effects based on gender and education stream which showed that males from science stream are better leaders than males and females from art stream. Pearson correlation shows significant relationship between leadership and strategic management domains. Multiple regression analysis shows that leadership domains contribute towards strategic management and vice versa. Results of the study have provided practical implications for improvement of qualities in MARA education sector. The collaboration of MARA education sector and entrepreneur sector is crucial in order tto produce graduates and knowledge workers who are competitive with entrepreneurship orientation.